Pengenalan Website sebagai Media Informasi dan Promosi Desa - Panji Wijonarko; Rohmad Dwi Cahya; Bimbang Agus Purnomo; Wawan Iswanto; Burhanudin Burhanudin; Rasyan Akbar (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The activity of introducing the website as a medium for village information and promotion was carried out on August 24 2024 at the RW 01 Kalibaru Office Hall, targeting participants as residents of RW 01. Various objectives of this activity were the reason for this activity, but the main objective of this activity was to increase public awareness of the importance of promoting villages through digital platforms, especially in introducing the village's tourism, arts and cultural potential to a wider audience. Regarding the method used in this activity, the activity of introducing this website includes socialization, scanning barcodes to access the website, as well as extracting information related to village potential that is not widely known. Resource persons and moderators or guides involved in this activity include Panji Wijonarko M.Kom, Rohmad Dwi Cahya, Bimbang Agus Purnomo, Wawan Iswanto, Burhanudin, and Rasyan Akbar. As expected, the results of this activity show that village residents are able to accept and understand the importance of using websites as an effective promotional tool. As a result, this activity succeeded in introducing the concept of village promotion via the internet, which is expected to not only increase the number of tourists visiting, but also strengthen residents' awareness of the importance of digital promotion strategies in village development.